2022
DOI: 10.3390/foods11040563
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Fermented Papaya in Human Health

Abstract: Fermented foods have been used for several years all over the world, due to their unique nutritional characteristics and because fermentation promotes conservation and food security. Moreover, fermented foods and beverages have a strong impact on human gut microbiota. Papaya is the fruit of the Carica papaya plant, traditionally used as a medicinal fruit, but there are also references to the use of the fermented form of this fruit. The main purpose of this review is to provide an improved understanding of ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
0
13
0
1
Order By: Relevance
“…The remarkable increase in TPC in fortified yoghurts is likely due to the presence of phenolic compounds in plant ingredients (Pelaes Vital et al ., 2015; Zhang et al ., 2019; Ahmed et al ., 2021). Papaya contains a wide range of phytochemicals such as phenolic compounds, carotenoids, glucosinolates, and alkaloids (Leitão et al ., 2022; Wani & Uppaluri, 2022). Besides, papaya seeds are a good source of phenolic compounds, including benzyl isothiocyanate, glucosinolates, β‐carotene, and carotenoids (Leitão et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remarkable increase in TPC in fortified yoghurts is likely due to the presence of phenolic compounds in plant ingredients (Pelaes Vital et al ., 2015; Zhang et al ., 2019; Ahmed et al ., 2021). Papaya contains a wide range of phytochemicals such as phenolic compounds, carotenoids, glucosinolates, and alkaloids (Leitão et al ., 2022; Wani & Uppaluri, 2022). Besides, papaya seeds are a good source of phenolic compounds, including benzyl isothiocyanate, glucosinolates, β‐carotene, and carotenoids (Leitão et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Papaya contains a wide range of phytochemicals such as phenolic compounds, carotenoids, glucosinolates, and alkaloids (Leitão et al ., 2022; Wani & Uppaluri, 2022). Besides, papaya seeds are a good source of phenolic compounds, including benzyl isothiocyanate, glucosinolates, β‐carotene, and carotenoids (Leitão et al ., 2022). On the other hand, bioavailability and physicochemical and nutritional properties of both starches and phenolic compounds were reported to be greatly affected by the starch‐polyphenol interactions (Zhu, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Our research team gathered the different benefits of the existing fermented papaya in the current market in a review article that highlights the benefits of several brands of fermented papaya supplements in human health [5]. Various experiments to determine its biological activity have been executed.…”
Section: Introductionmentioning
confidence: 99%
“…Relativamente à papaia fermentada, uma revisão já realizada por esta equipa de investigação (Leitão et al, 2022) encontrou vários estudos que relatam atividade antioxidante (Marotta et al, 2010;Marotta et al, 2006), propriedades antidiabéticas (Danese et al, 2006) e antidislipidémicas (Roohbakhsh et al, 2017). No entanto, para a obtenção de um produto eficaz e seguro, o processo fermentativo deve ser bem definido laboratorialmente com vista à obtenção de um processo padronizado de produção.…”
Section: Introductionunclassified
“…Regarding fermented papaya, a review conducted by this research team (Leitão et al 2022) found several studies reporting antioxidant activity (Francesco Marotta et al 2010;Franceso Marotta et al 2006) antidiabetic properties (Danese et al 2006) and antidyslipidemic properties (Roohbakhsh, Karimi, and Iranshahi 2017). However, to obtain an effective and safe product, the fermentation process must be welldefined in the laboratory to obtain a standardized production process.…”
Section: Introductionmentioning
confidence: 99%